School conflicts: Causes and management strategies in classroom relationships - Valente, Sabina (2022)
Conflicts cannot cease to exist, as they are intrinsic to human beings, forming an integral part of their moral and emotional growth. Likewise, they exist in all schools. The school is inserted in a space where the conflict manifests itself daily and assumes relevance, being the result of the multiple interpersonal relationships that occur in the school context. Thus, conflict is part of school life, which implies that teachers must have the skills to manage conflict constructively. Recognizing the diversity of school conflicts, this chapter aimed to present its causes, highlighting the main ones in the classroom, in the teacher-student relationship. It is important to conflict face and resolve it with skills to manage it properly and constructively, establish cooperative relationships, and produce integrative solutions. Harmony and appreciation should coexist in a classroom environment and conflict should not interfere, negatively, in the teaching and learning process. This bibliography review underscores the need for during the teachers’ initial training in conflict management skills development.